Cretaceous magmatism and metallogeny in the Bangong-Nujiang metallogenic belt, central Tibet: Evidence from petrogeochemistry, zircon U-Pb ages, and Hf-O isotopic compositions - Li, G.; Qin, K.; Li, J.; Evans, Noreen; Zhao, J.; Cao, M.; Zhang, X. (2015)
Porphyry Cu–Au and porphyry–skarn Cu ± Au ± Mo deposits are widely distributed in the Bangong–Nujiang metallogenic belt, central Tibet. Zircon U–Pb dating has revealed that Cretaceous ore-bearing intrusions related to Cu ± Au ± Mo mineralization formed in two periods (118–115 Ma and 90–88 Ma). These primarily high-K calc-alkaline series intrusions show light rare earth element enrichment (LaN/YbN = 6.06–20.2) and negative to no Eu anomaly (Eu*/Eu = 0.39–1.02). On primitive mantle-normalized diagrams, all the intrusions show strong enrichments in large ion lithophile elements (e.g., Cs, Rb, and K), depletions in Nb, Ta, and Ti, and negative Ba anomalies characteristic of arc magma. These intrusions show a wide range of zircon εHf(t) values from –6.3 to + 10.9 and δ18O values from 5.82 to 10.82 ‰, suggesting variable contributions from mantle and crustal sources. Considering the ~ 100 Ma Lhasa–Qiangtang collision, the 118–115 Ma magmas and related deposits were likely formed by melting of subduction metasomatized mantle wedge in a continental arc setting during northward subduction of the Bangong–Nujiang ocean, and then further evolved in the upper crust as a result of MASH processes. The younger 90–88 Ma ore-bearing magmas were potentially derived from melting of previously metasomatized lithospheric mantle during slab tear and break-off after the Lhasa–Qiangtang collision.